Clinical effect of ethanol co-use in patients with acute drug toxicity involving the use of central nervous system depressant recreational drugs. (8th April 2022) - Heier, Eva-Carina; Eyer, Florian; Rabe, Christian; Geith, Stefanie; Dargan, Paul I.; Wood, David M.; Heyerdahl, Fridtjof; Dines, Alison M.; Giraudon, Isabelle; Erik Hovda, Knut; Yates, Chris; Vallersnes, Odd Martin; et al.
Abstract : Background and importance: Patients who use recreational drugs frequently co-ingest ethanol, which is considered a central nervous system (CNS) depressant. The clinical relevance of this in acute toxicity involving other CNS depressants is not well described. Objective: To assess the clinical impact of ethanol co-use in patients presenting to the emergency department (ED) with acute toxicity involving the use of CNS depressant drugs. Design, settings and participants: A retrospective multicentre study using data from the Euro-DEN Plus database from January 2014 to December 2019. Outcomes measure and analysis: Comparison of epidemiologic and clinical characteristics, ED and hospital management of patients with CNS depressant intoxication with or without ethanol co-use. Main results: Although 7644 (17.5%) of the 43 633 presentations were included, ethanol was co-ingested in 3811 (49.9%). In total 53.3% required medical treatment, 14 patients died. Patients with ethanol co-use more frequently presented with a Glasgow Coma Scale (GCS) ≤8 (34.1% vs. 22.4%; P   <  0.001), vomiting (8.1% vs. 4.6%; P   <  0.001), anxiety (12 % vs. 6.4%; P   <  0.001), agitation/aggression (22% vs. 14.7%; P   <  0.001), seizures (3.8% vs. 2.4%; P   <  0.001) and hypotension (7.5% vs. 4.6%; P   <  0.001). They more often required ambulance transport (85.5% vs. 76.5%; P   <  0.001), medical treatment (57.3% vs. 48.0%; P   <  0.001), hospitalization (27.7% vs. 18.9%; P   <  0.001), and admission to intensive care (12.2% vs. 4.0%; P   <  0.001). Subgroup analysis showed that GCS ≤8 was particularly common in patients who combined ethanol with opioids or gamma-hydroxybutyrate (GHB)/gamma-butyrolactone (GBL). Conclusion: Co-use of ethanol with CNS-depressant drugs appears to increase the risk of adverse effects and is associated with a higher need for medical treatment, especially when ethanol is combined with opioids or GHB/GBL.